Seismic performance of older R/C frame structures accounting for infills-induced shear failure of columns. (1st September 2016) - Mohammad, Aslam Faqeer; Faggella, Marco; Gigliotti, Rosario; Spacone, Enrico
Highlights: Seismic performance of older infilled frames is assessed including shear failures. Nonlinear pushover and IDA analyses are performed at different limit states. Nonlinear shear in columns highly increases vulnerability of fully infilled frames. Columns shear failure with weak infills results in a more ductile behavior. Open bays location alter the global mechanism from ductile to more brittle. Abstract: Older infilled frame R/C structures have several deficiencies as compared to seismic code-conforming structures, inherent to the behavior of the structural elements and interaction between structural and nonstructural components, which should be accounted for an accurate performance assessment. In order to investigate the importance of incorporating the contribution of the infills (typically considered as non-structural members) and their interaction with non-ductile columns in a building structural model, a comprehensive performance based earthquake assessment over a range of hazard levels is carried out through Nonlinear static and Incremental Dynamic Analyses of a 2D frame model incorporating: (1) fiber section axial force–moment interaction, (2) cracking and crushing of the infills and (3) infills-induced shear failure of columns. The analyses are performed on three different common structural configurations: (A) bare frame, (B) uniformly infilled frame, and (C) partially infilled frame (pilotis frame). Results show the importance of correctly accounting for shear failure of columns when modeling the infill–frame interaction, and the influence of the inelastic shear law, opening placement, type of infills, and choice of infill constitutive model.